Environmental enrichment protects against functional deficits caused by traumatic brain injury - Johnson, Erica M. (Frontiers in Behavioral Neuroscience, 2013)
Environmental enrichment (EE) increases cortical weight, neuronal density, dendritic branching, and angiogenesis, all of which may be critical for functional recovery following insult. Our study was designed to determine possible benefits of pre-exposure to EE in preventing functional deficits following traumatic brain injury (TBI) to the prefrontal cortex. To examine the benefit of EE, adult male rats were placed in an enriched environment for 15 days. Enrichment was provided through social interaction, exercise, olfactory stimulation, and new objects/toys to explore. Following enrichment, experimental and age-matched controls were subjected to a moderate medial prefrontal cortex injury via controlled cortical impact. After one week recovery, animals were behaviorally tested to assess memory, anxiety, and sensory neglect. Lesion-induced deficits in spatial memory (Morris water maze) were significantly attenuated in EE pre-exposed rats 18-21 days following injury. In addition, TBI-induced sensory neglect was significantly reduced in EE rats relative to non-enriched animals. No differences in anxiety-like behavior on the elevated plus maze (EPM) were detected. The behavioral data suggest that EE is neuroprotective when applied prior to TBI, resulting in improved recovery following injury.